PENGARUH ADOPSI DEBIT CARD DAN E-MONEY TERHADAP POLA BELANJA KONSUMEN - Rahma, Niken; Widiyanti, Dwi Retno (Contemporary Studies in Economic, Finance and Banking, 2024)
The adoption of debit card and E-Money is increasingly important to study due to its potential to influence payment patterns and overall consumer behavior. This research aims to analyze the effect of debit cards and e-money on consumer shopping behavior. The subjects of this study are students from the Faculty of Economics and Business at Universitas Brawijaya, cohorts 2020, 2021, and 2022, who have been using debit card and E-Money for more than one year and receive an allowance of more than IDR 1,000,000. The sampling method used is purposive sampling, with a total of 104 respondents. Data were collected through questionnaires and analyzed using inferential quantitative methods with the Structural Equation Modeling Partial Least Squares (SEM-PLS) approach. The results indicate that debit cards and e-money significantly enhance consumer shopping behavior. These findings have important implications for governments, companies, and individuals in adopting digital payment technologies as part of a more effective financial management strategy.